2009
DOI: 10.4102/jamba.v2i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Cotton farmers’ vulnerability to climate change in Gokwe District (Zimbabwe): impact and influencing factors

Abstract: This study analyzes the vulnerability of cotton farmers to climate change in a cotton growing district in Zimbabwe. The vulnerability indicators studied include cotton output and farmers’ livelihoods from cotton farming. In order to examine climate variability and change, a time series analysis of two variables: temperature and rainfall was done for a period of 30 years, resulting in graphs of any climate anomalies. Correlation tests between the independent variable (the climate) and the dependent variable (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…Our locations include Scotland, Australia, New Zealand (two unique locations), and California and the ''Midwest'' in the United States. While the primary agricultural sector in all of these locations only provides relatively small contributions to respective national economies, in general, the farms are much larger in scale than in low-income countries where these types of studies are frequently conducted (see for example Gbetibouo 2009;Gwimbi 2009;Mertz et al 2009). The farmer surveys were all conducted for different purposes in these regions but contained similar enough questions that a comparison is useful and informative.…”
Section: Study Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our locations include Scotland, Australia, New Zealand (two unique locations), and California and the ''Midwest'' in the United States. While the primary agricultural sector in all of these locations only provides relatively small contributions to respective national economies, in general, the farms are much larger in scale than in low-income countries where these types of studies are frequently conducted (see for example Gbetibouo 2009;Gwimbi 2009;Mertz et al 2009). The farmer surveys were all conducted for different purposes in these regions but contained similar enough questions that a comparison is useful and informative.…”
Section: Study Locationsmentioning
confidence: 99%
“…It is known that propensity to act in response to potential natural hazards can depend largely on beliefs about the existence of the hazard and the perceptions of risks associated with it (Nigg and Mileti 2002). A great deal of work has been undertaken in low-income countries to understand what farmers believe about climate change and their perceptions of climate risks (see e.g., Gwimbi 2009;Maddison 2007), but less work has been conducted within highincome countries where agricultural systems can be quite different in scale and scope. Understanding what highincome country farmers believe about climate change and their risk perceptions will help to inform future mitigation and adaptation strategies in those regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Kurukulasuriya and Mendelsohn (2008), Deressa and Hassan (2009), Molua and Lambi (2007), and Gwimbi (2009) also revealed that decreased rainfall or increased temperatures reduce cotton yield, which led to a reduction in net revenues in Africa. These results were also confirmed by the findings in Ouedraogo et al (2006) in which the Ricardian approach was used to evaluate the relationship between net farm values and climate change.…”
Section: Economic Impact Of Change In Cotton Yieldmentioning
confidence: 99%
“…In a recent survey [22] more than 70% of farmers surveyed in one district in Zimbabwe highlighted the lack of access to timely weather forecasts, climate change information and credit facilities that were needed to motivate them in waterconservation strategies, as constraining their ability to adapt. Poverty posed a major bottleneck for farmers that did not have the necessary technology and resources to change or to adapt to the rigours of climate change.…”
Section: Determinants Of the Ability To Adapt (Adaptive Capacity)mentioning
confidence: 99%
“…In cotton producing areas such as Gokwe in Zimbabwe, the preferred adaptation measures include use of irrigation, diversification into more drought-resistant varieties, diversifying into other crops, and timing the planting period to coincide with the onset of the rains [22].…”
Section: Strategies For Adaptationmentioning
confidence: 99%